(untitled) (The Review of Diabetic Studies, 2025)
Cancer poses not only a physical health challenge but also a profound psychological and social burden on patients and their families. In Saudi Arabia, where cancer incidence is rising, psychosocial support has emerged as a critical component of holistic cancer care, particularly in alignment with Saudi Vision 2030, which emphasizes patient-centered healthcare transformation and quality-of-life enhancement. This mixed-methods systematic review aims to explore the psychosocial support needs of cancer patients in Saudi Arabia by synthesizing quantitative data on the prevalence of psychological distress and qualitative insights into lived experiences. Using PRISMA guidelines, studies published between 2016 and 2024 were systematically analyzed from major international and regional databases. Findings reveal that cancer patients in Saudi Arabia experience high levels of anxiety, depression, fear of recurrence, social isolation, and spiritual distress, with significant unmet psychological needs due to stigma, limited access to professional counseling, and insufficient integration of psychosocial services in oncology care. Qualitative evidence highlights the importance of religion, family involvement, and culturally sensitive support models. The review concludes that integrating psychosocial care within oncology services is pivotal to achieving Vision 2030 objectives. Strategic recommendations include training oncology teams in psychosocial care, establishing psycho-oncology clinics, and implementing digital mental health platforms to enhance accessibility and patient well-being.